Pengaruh Likuiditas dan Inventory Turnover terhadap Profitabilitas CV Mutiara Abadi Bogor - Faisal Salistia; Evinovita Evinovita; Eneng Siti Khodijah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2019)
Profitability is the ability of companies to obtain profits generated from company activities to measure how much management effectiveness in managing assets owned by the company to generate profits. This study uses return on assets (ROA) to measure the profitability of a company, because ROA shows the rate of return of all company assets not just equity investment. This study uses a quantitative method with a type of causal research because it is adjusted to the hypothesis formulation that predicts that liquidity (current ratio) (CR) and inventory turnover (ITO) affect ROA. The data used in this study are quantitative data obtained from secondary data from quarterly financial reports CV. Abadi Bogor Bogor in 2012-2016 with documentation data collection methods. Multiple linear regression analysis in this study was used to determine the effect of independent variables (CR and ITO) on the dependent variable (ROA). Based on the results of statistical calculations show that the variable liquidity (current ratio) partially has a positive effect on ROA of the company CV. Abadi Abadi Bogor for the period 2012-2016. Partial Inventory Turnover has no significant effect on ROA of a company CV. Abadi Abadi Bogor for the period 2012-2016. While simultaneously variable liquidity (current ratio) and inventory turnover have a positive effect on ROA of the company CV. Abadi Abadi Bogor for the period 2012-2016.